Comparison of 2D and 3D Stability Analyses for Natural Slope - Bahsan, Erly; Fakhriyyanti, Rifani (International Journal of Engineering and Technology, 2018)
Slope stability analyses are performed mostly as a two-dimensional (2D) section under the assumption of plane strain conditions, without much consideration to the impact of three-dimensional (3D) shapes. For natural slopes that have the complexities of slope surfaces, 3D modeling may also be considered since it can represent the more realistic geometry of the slope. However, previous studies show that the factor of safety (FS) as a result of 3D analyses mostly overestimated the FS from 2D analyses. This may lead to a long discussion on whether the 3D analysis is still applicable for the natural slopes, and could it represent the same results as the 2D analysis. This study was conducted using the finite element method for calculating the 2D and 3D FS of Pasir Muncang natural slope in order to observe differences of FS resulted from both analyses. A comparison of the FS from the 2D and 3D analyses, and also verification of sensitivity on several factors that impact the 2D and 3D models have been performed. The results of this study has indicated that some factors such as soil parameters, contour interval, and mesh coarseness greatly affect the results of the 2D and 3D calculations. Having carefully selected the aforementioned factors as the inputs for calculations, the difference between the FS values of 3D and 2D analyses becomes smaller. The final result of FS for this case study from the 3D analysis was still higher than the one from the 2D analysis, with the ratio of FS from 3D to FS from 2D was 1.44. It can be inferred that the use of 3D analyses needs more accurate data selections compared to the 2D analyses.Â Â